(untitled) (Global Journal of Management and Business Research, 2014)
This study investigated the impact that methods of selecting incentive schemes had on the characteristics manifested by the schemes while being used by construction firms in Nigeria. One hundred and four project managers of forty randomly selected construction firms participated in a questionnaire survey to determine the characteristics exhibited by incentive schemes based on the methods employed for their selection. Findings revealed that for the study-based selection method and the selection based on performance measurement, the use of incentive schemes did not cause reduction in the quality of work, unhealthy competition among workers nor fight among themselves. While selection based on tradition and discretion. caused the following; reduced quality of work, fighting among workers and generated unhealthy competition among workers. The study therefore recommended the use of the study-based selection and the selection based on performance measurement for incentive schemes used in the construction industry.